Effects of Vitamin E in the Management of Dyslipidemia in Combination with Statin Therapy - Ishaque Bhatti, Muhammad; Bano, Razia; Rizwan Memon, Fazeela; Shah, Madiha; Memon, Rizwan Ahmed; Memon, Ali Raza (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the effects of vitamin E therapy in the management of dyslipidemia with combination of statin drugs and also to determine the efficacy of statin drugs with combination of vitamin E therapy. Methodology: This case control study was conducted at LUMHS Jamshoro. Total 200 patients of dyslipidemia with the age between 30 to 50 years were included with mentioned inclusion and exclusion criteria & aere divided in to two groups; control group who received only statin drugs for treatment of dyslipidemia and case control group who received station drugs along with Vitamin E 800 mgs in divided dose.The fasting blood glucose level was measured by glucose oxidase method while lipid profile parameters serum cholesterol, TG’s, Serum LDL levels were estimated byenzyme caloric method on Cobas auto analyzer (model c-111 ACN 435 GERMANY) while HbA1c% was estimated on microlab. The statistical analysis was done on SPSS version 21 by applying unpaired student t test and ANOVA. The p value less than 0.05 consider as significant. Results: Finally after treatment phase the Mean & SD value of serum cholesterol in control group was 209.13 ± 5.15 mg/dl while in case study group was 189.51 ± 6.11 mg/dl , serum TG’s levels in control group was 191.52 ± 7.83 mg/dl & case study group was 168.56 ± 7.81 mg/dl, serum LDL levels in control group was 120.44 ± 4.67 mg/dl & in case study group was 97.15 ± 5.76 mg/dl. All parameters of lipid profile significantly decline in case study group. Conclusion: This research concluded that there is strong positive impact of vitamin E along with statin therapy on the management of dyslipidemia and in prevention of cardiovascular complications.